Magical words & iceberg territory : an exploration of the multifunctionality of language in dramatic dialogue, with specific reference to selected Fugard plays - Cunliffe, Rozanne Mary (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2000.